The assessment of fishery status depends on fish habitats. Issue 1 (11th September 2018) - Brown, Christopher J.; Broadley, Andrew; Adame, Maria F.; Branch, Trevor A.; Turschwell, Mischa P.; Connolly, Rod M.
Abstract: At the crux of the debate over the global sustainability of fisheries is what society must do to prevent over‐exploitation and aid recovery of fisheries that have historically been over‐exploited. The focus of debates has been on controlling fishing pressure, and assessments have not considered that stock production may be affected by changes in fish habitat. Fish habitats are being modified by climate change, built infrastructure, destructive fishing practices and pollution. We conceptualize how the classification of stock status can be biased by habitat change. Habitat loss and degradation can result in either overly optimistic or overly conservative assessment of stock status. The classification of stock status depends on how habitat affects fish demography and what reference points management uses to assess status. Nearly half of the 418 stocks in a global stock assessment database use seagrass, mangroves, coral reefs and macroalgae habitats that have well‐documented trends. There is also considerable circumstantial evidence that habitat change has contributed to over‐exploitation or enhanced production of data‐poor fisheries, like inland and subsistence fisheries. Globally many habitats are in decline, so the role of habitat should be considered when assessing the global status of fisheries. New methods and global databases of habitat trends and use of habitats by fishery species are required to properly attribute causes of decline in fisheries and are likely to raise the profile of habitat protection as an important complementary aim for fisheries management.